Pengaruh Pendampingan Gosok Gigi yang Benar terhadap Peningkatan Kesadaran Kesehatan Gigi dan Mulut pada Siswa SDN 3 Asrikaton, Kabupaten Malang: "The Influence of Proper Tooth Brushing Mentoring on the Improvement of Dental and Oral Health Awareness among Students at SDN 3 Asrikaton, Malang Regency." - Yulianti, Eny (Jurnal Surya, 2024)
The World Health Organization (WHO) asserts that the global health indicator target for oral health is the maintenance of dental and oral health from childhood and adolescence through old age. The oral health of children significantly influences the development of their teeth. One of the efforts to ensure good dental and oral health is by increasing awareness of dental health through education on proper tooth brushing techniques. This community service involves mentoring on the correct method of tooth brushing and maintaining dental and oral health, taking place at SD Negeri 3 Asrikaton, Malang, East Java. The community service method employed includes providing theoretical materials and practical guidance on proper tooth brushing techniques. The results indicate an increase in students' awareness of maintaining dental and oral health, as evidenced by the growing number of students engaging in tooth brushing before bedtime.